(untitled) (International Journal of Nursing Education, 2021)
With a view to assess the level of stress among staff nurses working in psychiatric and multi specialityhospitals, a non- experimental comparative study with descriptive approach was undertaken among 120Staff Nurses. Simple random sampling techniques were used in selecting the staff nurses. The result revealedthat 56.7% moderate stress in psychiatric hospital nurses and 65% in multispeciality hospital nurses arehaving severe stress level.